Results of bird ringing in Poland : migrations of dunlin Calidris alpina - Gromadzka, Jadwiga (Państwowe Wydawnictwo Naukowe, 1983)
Dunlins, belonging mainly to the nominate race Calidris alpina alpina, were ringed in Poland between 1960-1980 during their autumn passage at Gdansk Bay. To the end of 1980 18 118 birds were ringed, about which 372 long-distance recoveries were obtained. In 1978, the ringing of breeding C. alpina schinzii was begun in the local breeding colony, where 150 nestlings and adults were ringed. Dunlins ringed in Poland during autumn migrate mainly in the western and south-western directions. Single birds migrate south-east. Their wintering grounds are on the coasts of the whole of Western Europe, in the Mediterranean basin and on the coasts of North-western Africa. Some differences were found between juveniles and adults: the recovery rate of juveniles is higher than that of adults, juveniles migrate more slowly than adults, and the general direction of their migration is more con¬tinental. Half of the recoveries of dunlins ringed in Poland concern birds which were killed, by man.
S. 113-136 : il. ; 24 cm
Keywords: Biegus zmienny -- migracja [KABA]; Ptaki -- obrączkowanie -- Polska [KABA]; Dunlin; bird migration; bird banding; Poland; sandpipers; birds; Calidris alpina; Scolopacidae; Aves